Critical Discourse Analysis of Benyamin Netanyahu ICC Open Hearing Session and Radar JawaPos Statement on Israel-Palestine Conflict - Nur Laily Arifiyah; Nurranafi Syam Maella; Zulaikha Zulaikha (Journey: Journal of English Language and Pedagogy, 2024)
This study aimed to analyze the speech by Israeli Prime Minister Benjamin Netanyahu in response to the ICC arrest warrant against Israeli leaders.. This study took a qualitative method with critical discourse analysis based on Norman Fairclough's theory. The subject of the research was the speech by Israeli PM Benjamin Netanyahu taken from the YouTube channel Forbes Breaking News, posted on May 21, 2024, titled "Israeli PM Benjamin Netanyahu Responds to Arrest Warrant." This research aimed to provide a deep understanding of the discursive strategies used by Israeli PM Benjamin Netanyahu in his speech. The analysis revealed that Netanyahu's speech constructed a strong moral opposition and employed discursive strategies to legitimize Israel's actions and discredit the Israeli Criminal Court (ICC) and Hamas. Netanyahu’s speech used complex discursive strategies to influence public and international perception. Through the use of emotional language, historical analogies, and criticism of the ICC, Netanyahu effectively built a narrative supporting Israel’s position in the conflict with Hamas. This analysis demonstrated how political discourse could be used to shape power and legitimacy in the context of international politics.